Determining the potential indigenous red-yeasts producing β-carotene and their phylogenetic relationship - I Nyoman Sumerta; Yeni Yuliani; Atit Kanti (Journal of Microbial Systematics and Biotechnology, 2019)
Red-yeasts are pigmented yeast species that could synthesize carotenoids for food supplements and pharmaceutical purposes. However, this group contains a lot of species which need to be explored thoroughly. The objective of this study was to view the β-carotene production of three indigenous red-yeasts by modifying glucose content in the growth medium and verifying their phylogenetic relationship. The glucose content modification in growth media influenced the β-carotene production of each species. Rhodosporidiobolus ruineniae (InaCCY1638/Y15Eg075) and Rhodosporidiobolus poonsokiae (InaCCY1606/Y15Kr068) produced higher β-carotene than Rhodotorula paludigena (InaCCY1527/Y15Eg004). These Rhodosporidiobolus species were able to produce higher β-carotene from 0.5 to 2% glucose content while Rhodotorula was low production in 2% glucose content. The higher producers by Rhodosporidiobolus species were clustered to Ruineniae clade and could be a potential clade for higher β-carotene production. Based on this result, using a high carotenoid producer of red-yeasts from indigenous strains is potential to be developed for β-carotene bioindustry in the future.